Analisis Pengaruh Kinerja Keuangan dan Corporate Social Responsibility (Csr) Terhadap Nilai Perusahaan Pertambangan Selama Covid-19 Tahun 2020-2021 - Dwi Anggara Ristami; Lukman Efendy; Nurabiah (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze the effect of financial performance proxied by Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) on the value of mining sector companies listed on the Indonesia Stock Exchange (IDX) during the Covid-19 pandemic in 2020, 2021, and 2022. The number of samples in this study is 37 companies.. The data analysis technique used multiple linear regression with the help of the SPSS version 27 application. The results of the study showed that ROA had a significant effect on company value, which means that the efficiency of using company assets in generating profits can increase company value. ROE also had a significant effect on company value, indicating that return on equity is an important consideration for investors. NPM also has a significant effect on company value, which means that the company’s efficiency in managing costs and generating profits from sales and increasing investor confidence can increase the company’s value. Based on these results, it is concluded that financial performance is an important factor in influencing company value, especially in the midst of economic uncertainty such as the Covid-19 pandemic.